The mediating role of organizational cynicism in the effect of distributional justice on intention to leave the job - Gezici, Nurcan; Aytekin, Mehmet; Rençber, Ömer Faruk (Global Advances in Business Studies, 2025)
This study aims to investigate the effect of distributive justice on intention to leave the job and to determine the mediating role of organizational cynicism in this relationship. To this end, the perceptions of distributive justice, organizational cynicism, and intention to leave the job were measured among administrative and healthcare employees of private hospitals. The main population of the study consists of employees of private hospitals operating in Gaziantep. The sample of the research consists of healthcare and administrative staff of private hospitals in the Şahinbey and Şehitkamil districts of Gaziantep. The analysis results indicated that distributive justice had a negative and significant effect on intention to leave, distributive justice had a negative and significant effect on organizational cynicism, and organizational cynicism had a positive and significant effect on intention to leave. When adding the mediating role of organizational cynicism to the model when measuring the effect of distributive justice on intention to leave, this effect was reduced according to the simple linear regression results.